Pembelajaran Musik Berbasis Aplikasi Musescore 3 - Alwan Alwan Hafiz; Hary Murcahyanto; M. Ridwan Markarma; Laelatul Asyro (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the effect of the MuseScore 3 application on music learning outcomes for school students. This study uses a quantitative method with a true experimental approach with a Post-test Only Control Design research design. This study used two groups of subjects as samples, namely the control group and the experimental group. The samples of this study were students of class X IPS and X IPA with a total sample of 49. The sampling technique used total sampling, and the data analysis technique used a different test (t-test). The results showed that there were differences in learning outcomes between students who were taught using the MuseScore 3 application media and students who were not taught using the MuseScore 3 application media. This was indicated by the post-test average score of the experimental group, which was 79.06 higher than the average score. the control group's post-test average was 73.57. The t-count value is 2.589 and the significance value (ðœŒ) is 0.013. From these results, it can be concluded that Ho is rejected, and Ha is accepted, because t-count > t-table value, 2.589> 2.408, and the significance value <0.05 (two-party test), 0.013 <0.05. Keywords: Application, Media, Music Learning, MuseScore 3